2022
DOI: 10.1177/03611981221104807
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of Rail Transit Costs and Cost Effectiveness

Abstract: Previous research has evaluated the temporal variability of transit costs and shown that peak period service costs more to operate in both gross and net terms. However, research on spatial variability of transit costs, particulalry for modes other than bus transit, is quite limited. Using transit agency data on labor and train allocations in the United States, I develop an accounting cost model that allocates variable and semi-fixed capital costs to times of day and each link and station of two regional rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…To do this, I use FY19 OD fare data provided by BART and MARTA, as well as ndings from the cost allocation study (Mallett, 2022) I do not control for directionality in my analysis; a trip from one station to another is analyzed in tandem with a trip in the reverse direction. Again, for consistency in analysis, I include only mainline tracks of the BART network (i.e., where traditional BART trains/technology operate), so exclude any trips that solely use non-mainline portions of track.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To do this, I use FY19 OD fare data provided by BART and MARTA, as well as ndings from the cost allocation study (Mallett, 2022) I do not control for directionality in my analysis; a trip from one station to another is analyzed in tandem with a trip in the reverse direction. Again, for consistency in analysis, I include only mainline tracks of the BART network (i.e., where traditional BART trains/technology operate), so exclude any trips that solely use non-mainline portions of track.…”
Section: Methodsmentioning
confidence: 99%
“…Measuring cost recovery variability amounts to analyzing how costs and fare receipts covary across time and space. I document cost and cost per rider variability in the cost allocation study (Mallett, 2022). In brief, I found that costs decrease but costs per rider increase with distance from the core of the BART system, that there is no clear spatial pattern in the MARTA system, and that the weekday peak period -out of eight operating time periods for BART and ve for MARTA -has the lowest cost per rider in both networks but the highest cost for BART and barely lower costs than the weekday base period for MARTA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations